Benzenetriol-Derived Compounds against Citrus Canker - Cavalca, Lúcia Bonci; Lahive, Ciaran W.; Gijsbers, Fleur; Pavan, Fernando Rogério [UNESP]; Scheffers, Dirk-Jan; Deuss, Peter J. (MDPI, 2021)
In order to replace the huge amounts of copper salts used in citrus orchards, alternatives have been sought in the form of organic compounds of natural origin with activity against the causative agent of citrus canker, the phytopathogen Xanthomonas citri subsp. Citri. We synthesized a series of 4-alkoxy-1,2-benzene diols (alkyl-BDOs) using 1,2,4-benzenetriol (BTO) as a starting material through a three-step synthesis route and evaluated their suitability as antibacterial compounds. Our results show that alkyl ethers derived from 1,2,4-benzenetriol have bactericidal activity against X. citri, disrupting the bacterial cell membrane within 15 min. Alkyl-BDOs were also shown to remain active against the bacteria while in solution, and presented low toxicity to (human) MRC-5 cells. Therefore, we have demonstrated that 1,2,4-benzenetriol-a molecule that can be obtained from agricultural residues-is an adequate precursor for the synthesis of new compounds with activity against X. citri.
Keywords: antimicrobials; bio-based chemicals; lignocellulosic biomass; phenolic compounds; Xanthomonas citri